Combining Multi-Band Power System Stabilizers and Hybrid Power Flow Controllers to Support Electricity Grids with High Penetration of Distributed Renewable Generation - Zahira Seddiki; Tayeb Allaoui; Mohamed Bey; Mouloud Denai (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
The paper demonstrates the application of a new power flow configuration consisting of a Hybrid Power Flow Controller (HPFC) and a Multi-Band Power System Stabilizers (MB-PSS) to enhance the performance of a multi-machine power network in the presence of solar photovoltaic (PV) and wind energy sources. The HPFC is a new type of FACTS (Flexible AC Transmission Systems) device, which has been introduced to address inter-area congestion problems by controlling the real power flow and providing voltage regulation. The MB-PSS, on the other hand, is a power system stabilizer based on different frequency modes of electromechanical oscillations, where the discontinuities caused by the faults in the grid are taken in consideration, for multiple fault clearing times.The multi-machine power network with PV and wind distributed generation and the proposed power flow configuration are simulated using Matlab/ SimPowerSystems Toolbox and analyzed under three phase to ground short-circuits faults occurring in the middle of transmission line.